ANALISIS PENGARUH EKONOMI DIGITAL TERHADAP PERTUMBUHAN EKONOMI DI INDINESIA - Lutfia Amara; Muhammad Irwan Padli Nasution (INTERNATIONAL, Journal of Sharia Business Management, 2025)
The development of information and communication technology has had a significant impact on economic dynamics in Indonesia. Increasingly widespread digitalization has driven the emergence of the digital economy as a key pillar in increasing national economic activity. The ease of transactions through electronic money and e-commerce accelerates the flow of goods and services and opens up new opportunities for businesses in various sectors. This situation illustrates the digital economy’s crucial role in strengthening competitiveness, expanding market access, and increasing the efficiency of economic activity. Furthermore, the rapid growth of the digital economy also demands infrastructure readiness, system security, and adaptive regulations to ensure its positive impacts are sustainable. With the increasing value of digital transactions, the Indonesian economy is showing signs of increasingly modern and inclusive development, while also emphasizing the importance of collaboration between the government, businesses, and the community in supporting technology-based economic growth.